Management dilemmas in acute pulmonary embolism. Issue 2 (16th December 2013) - Condliffe, Robin; Elliot, Charlie A; Hughes, Rodney J; Hurdman, Judith; Maclean, Rhona M; Sabroe, Ian; van Veen, Joost J; Kiely, David G
Abstract : Background: Physicians treating acute pulmonary embolism (PE) are faced with difficult management decisions while specific guidance from recent guidelines may be absent. Methods: Fourteen clinical dilemmas were identified by physicians and haematologists with specific interests in acute and chronic PE. Current evidence was reviewed and a practical approach suggested. Results: Management dilemmas discussed include: sub-massive PE, PE following recent stroke or surgery, thrombolysis dosing and use in cardiac arrest, surgical or catheter-based therapy, failure to respond to initial thrombolysis, PE in pregnancy, right atrial thrombus, role of caval filter insertion, incidental and sub-segmental PE, differentiating acute from chronic PE, early discharge and novel oral anticoagulants. Conclusion: The suggested approaches are based on a review of the available evidence and guidelines and on our clinical experience. Management in an individual patient requires clinical assessment of risks and benefits and also depends on local availability of therapeutic interventions.